2010
DOI: 10.1152/japplphysiol.01048.2009
|View full text |Cite
|
Sign up to set email alerts
|

Activations of TRPA1 and P2X receptors are important in ROS-mediated stimulation of capsaicin-sensitive lung vagal afferents by cigarette smoke in rats

Abstract: Capsaicin-sensitive lung vagal afferents (CSLVAs) are important in detecting pulmonary reactive oxygen species (ROS). We investigated the mechanisms underlying the stimulation of CSLVAs by inhaled cigarette smoke (CS) in 216 anesthetized rats. In spontaneously breathing rats, CS evoked a CSLVA-mediated reflex bradypnea that was prevented by N-acetyl-L-cysteine (NAC; an antioxidant), HC-030031 [a transient receptor potential ankyrin 1 (TRPA1) receptor antagonist], and iso-pyridoxalphosphate-6-azophenyl-2',5'-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 48 publications
0
51
1
Order By: Relevance
“…Subsequently, the experiments were repeated 15 min after pretreatment with HC-030031 (an antagonist of TRPA1 receptors; 8 mg/kg iv) (groups 8 and 9) or its vehicle (groups 10 and 11). The dose of HC-030031 was shown to exert a complete blocking effect on the stimulation of the CSLV fibers elicited by the TRPA1 receptor agonist in our previous study (25). The purpose of series 6 was to verify the effectiveness and specificity of the antagonizing effect of HC-030031 on the TRPA1 receptors under the present experimental conditions.…”
Section: In Vivo Studymentioning
confidence: 80%
See 2 more Smart Citations
“…Subsequently, the experiments were repeated 15 min after pretreatment with HC-030031 (an antagonist of TRPA1 receptors; 8 mg/kg iv) (groups 8 and 9) or its vehicle (groups 10 and 11). The dose of HC-030031 was shown to exert a complete blocking effect on the stimulation of the CSLV fibers elicited by the TRPA1 receptor agonist in our previous study (25). The purpose of series 6 was to verify the effectiveness and specificity of the antagonizing effect of HC-030031 on the TRPA1 receptors under the present experimental conditions.…”
Section: In Vivo Studymentioning
confidence: 80%
“…Fiber activity arising from CSLV afferents was recorded in the anesthetized, artificially ventilated rats by using the techniques described in our previous studies (14,(25)(26)(27). In brief, the trachea was cannulated and tracheal pressure was measured via a sideport of the cannula.…”
Section: In Vivo Studymentioning
confidence: 99%
See 1 more Smart Citation
“…TRPA1 can be activated by various chemical stimulants, including ROS (5,48). However, production of some arachidonic acid metabolites under oxidative stress may also activate TRPA1 receptors and then cause stimulation of LVCFs (33). Our results obtained from measurements of reflex apneic response and single-unit LVCF recording have demonstrated that administration of TRPA1 antagonists (HC-030031 or AP18) prevented the AIH-enhanced reflex apnea and LVCF sensitivity to capsaicin and ␣,␤-methylene-ATP.…”
Section: Discussionmentioning
confidence: 63%
“…Pretreatments with dimethylthiourea, Nacetyl-L-cysteine, vehicle of antioxidants, HC-030031, AP18, and vehicle of TRPA1 antagonists were made 15, 15, 15, 5, 5, and 5 min, respectively, before AIH exposure. The doses and treatment times with effectiveness for these drugs were adopted from previous studies (28,33).…”
Section: Methodsmentioning
confidence: 99%